2023
DOI: 10.3390/jcm12113853
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prognostic Factors of Painful Vertebral Compression Fracture Caused by Spine Stereotactic Body Radiotherapy

Abstract: Most studies of vertebral compression fractures (VCF) caused by stereotactic body radiotherapy (SBRT) do not discuss the symptoms of this complication. In this paper, we aimed to determine the rate and prognostic factors of painful VCF caused by SBRT for spinal metastases. Spinal segments with VCF in patients treated with spine SBRT between 2013 and 2021 were retrospectively reviewed. The primary endpoint was the rate of painful VCF (grades 2–3). Patient demographic and clinical characteristics were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In the SC.24 phase III trial, which compared the palliative effect between conventional EBRT and SBRT for painful spinal metastases, SBRT caused grade 3 VCF in 1% of the patients (1/110 patients) [ 7 ]. A retrospective case series at our institution found grade 3 VCFs in 1.9% of all the irradiated spinal segments (15/779 segments) [ 33 ]. On the other hand, several retrospective studies have reported a high grade 3 VCF occurrence rate of 15% (15/100 segments) and 21% (15/72 segments) [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the SC.24 phase III trial, which compared the palliative effect between conventional EBRT and SBRT for painful spinal metastases, SBRT caused grade 3 VCF in 1% of the patients (1/110 patients) [ 7 ]. A retrospective case series at our institution found grade 3 VCFs in 1.9% of all the irradiated spinal segments (15/779 segments) [ 33 ]. On the other hand, several retrospective studies have reported a high grade 3 VCF occurrence rate of 15% (15/100 segments) and 21% (15/72 segments) [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, VCF was not included in the DLT. We did not consider it relevant to the decision-making process because most SBRT-induced VCFs are painless [ 7 , 33 ]. However, the rare occurrence of a severe VCF (e.g., grade 3: intensely painful, requiring hospitalization or invasive interventions such as percutaneous cement injection or surgery) had a strong impact on the patient’s quality of life and influenced the treatment decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the VRMDS only captures information on radiation therapy, there was also a lack of data on the combination of SBRT with systemic therapies such as immunotherapy [ 39 ]. There was also a lack of important spine SBRT outcomes data in the dataset, including local control and symptom control outcomes, as well as toxicity outcomes such as vertebral fracture [ 40 , 41 ] and radiation myelopathy [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phase III SC.24 clinical trial demonstrated that spinal SBRT was superior to cEBRT in terms of pain relief and has therefore been established as one of the standard treatments [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is true that the limitations of spinal SBRT, as well as its possible complications, are known to a greater extent [20]. Possible complications include vertebral body fractures (VBF) (11-39%) and myelopathy (0.4%) [19,24]. Another possibility is the appearance of the "Pain Flare" effect (14-68%), a transient increase in pain that can be controlled with corticosteroids as a preventive measure.…”
Section: Introductionmentioning
confidence: 99%